2008
DOI: 10.1007/s11240-008-9393-x
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from in vitro leaves of mature black cherry (Prunus serotina)

Abstract: A regeneration system was developed for Prunus serotina from a juvenile (F) and two mature genotypes (#3 and #4). Adventitious shoots regenerated from leaves of in vitro cultures on woody plant medium with thidiazuron (TDZ) and naphthaleneacetic acid (NAA). The best regeneration for genotype F (91.4%) was observed on medium with 9.08 lM TDZ and 1.07 lM NAA. The highest mean number of shoots (8.2) was obtained on medium containing 9.08 lM TDZ and 0.54 lM NAA. Genotype #3 had the highest regeneration (41.7%) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 28 publications
7
38
0
1
Order By: Relevance
“…There are also no quantitative studies that examine the relation between the age of the explant tissue, or the age of the mother plant, and the level of contamination. Separately, the correlation between the age of the mother plant and regeneration efficiency has been reported in other species in which juvenile tissues generally resulted in better regeneration than tissues from adult mother plants or were less recalcitrant to regeneration (Liu and Pijut 2008, Cardoso and Habermann 2014, Lema-Rumińska and Kulus 2014. In addition, we observed that in most Dendrobium micropropagation studies that employed somatic tissues as explants, young shoots (0.5 to 12 cm long) were the main explant used rather than mature shoots with leaves or pseudobulbs (Tab.…”
Section: In Vivo Conditions Of Donor Plants and Explant Choicesupporting
confidence: 67%
“…There are also no quantitative studies that examine the relation between the age of the explant tissue, or the age of the mother plant, and the level of contamination. Separately, the correlation between the age of the mother plant and regeneration efficiency has been reported in other species in which juvenile tissues generally resulted in better regeneration than tissues from adult mother plants or were less recalcitrant to regeneration (Liu and Pijut 2008, Cardoso and Habermann 2014, Lema-Rumińska and Kulus 2014. In addition, we observed that in most Dendrobium micropropagation studies that employed somatic tissues as explants, young shoots (0.5 to 12 cm long) were the main explant used rather than mature shoots with leaves or pseudobulbs (Tab.…”
Section: In Vivo Conditions Of Donor Plants and Explant Choicesupporting
confidence: 67%
“…Similarly maximum number of shoots was achieved from leaf section callus of Hyptis suaveolens [34] on MS medium containing 0.5 mg/L BA and 0.5 mg/L GA 3 . In the present investigation, 71.6% of the organogenic calli derived through leaf section explants on MS medium supplemented with 1.0 mg/L TDZ and 0.25 mg/L NAA produced an average of 2.1 shoots per callus explant which was consistent with the previous reports such as, Saussurea obvallata [14] [39], Aechmea fasciata [40] and Echinacea purpurea [26]. Ghimire et al [41] obtained highest mean number (10.65) of shoots per explant from in vitro leaves of Drymaria cordata on medium containing 1.0 mg/L BA and 0.1 mg/L NAA.…”
Section: Discussionsupporting
confidence: 92%
“…A morfogênese, caracterizada pela emergência e formação de novos órgãos, resulta da interação de processos de indução, competência, determinação e diferenciação celular, os quais são influenciados pelo meio de cultivo, pelo genótipo, pelo tipo e pelas condições fisiológicas dos explantes, bem como pelas condições físicas do cultivo in vitro (LIU & PIJUT, 2008).…”
Section: Introductionunclassified